2020
DOI: 10.1093/jme/tjaa198
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition-Site Selection of Phlebotomus papatasi (Diptera: Psychodidae) Sand Flies: Attraction to Bacterial Isolates From an Attractive Rearing Medium

Abstract: Phlebotomine sand flies are worldwide vectors of Leishmania parasites as well as other bacterial and viral pathogens. Due to the variable impact of traditional vector control practices, a more ecologically based approach is needed. The goal of this study was to isolate bacteria from the most attractive substrate to gravid Phlebotomus papatasi Scopoli sand flies and determine the role of bacterial volatiles in the oviposition attractancy of P. papatasi using behavioral assays. We hypothesized that gravid sand f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Eggs are typically laid in soil rich in organic material on which the larvae feed and develop through four instars before pupation and adult emergence [ 15 ]. The coprophagic diet of larvae is consistent with the strong preference of New and Old World sand flies for different sources of decomposing organic matter, often from fecal sources [ 16 19 ], and there is strong evidence that microbes play an important role in mediating this attraction [ 20 , 21 ]. There is also some evidence that bacteria are beneficial for the development of larvae [ 20 ], but this concept is still poorly understood.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Eggs are typically laid in soil rich in organic material on which the larvae feed and develop through four instars before pupation and adult emergence [ 15 ]. The coprophagic diet of larvae is consistent with the strong preference of New and Old World sand flies for different sources of decomposing organic matter, often from fecal sources [ 16 19 ], and there is strong evidence that microbes play an important role in mediating this attraction [ 20 , 21 ]. There is also some evidence that bacteria are beneficial for the development of larvae [ 20 ], but this concept is still poorly understood.…”
Section: Introductionmentioning
confidence: 83%
“…It is possible that larval conditioning leads to a decrease in the relative abundance of bacteria that are unattractive or even repellent and/or to an increase in the relative abundance of bacteria that are attractive to sand flies. In a previous study, Kakumanu et al [ 21 ] identified three bacterial isolates ( Microbacterium sorbitolivorans , Bacillus zhangzhouensis , Sphingobacterium phlebotomi ) that were highly attractive to sand flies at low concentrations but were repellant at high concentrations. In contrast, Sphingobacterium daejeonense was repellent at low concentration but tended to be attractive (but not significantly so) at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations